2021
DOI: 10.3390/agronomy11081637
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Edaphic Crop Conditions on the Free Amino Acid Profile of PH-16 Dry Cacao Beans

Abstract: Free amino acids in cacao beans are important precursors to the aroma and flavor of chocolate. In this research, we used inferential and explanatory statistical techniques to verify the effect of different edaphic crop conditions on the free amino acid profile of PH-16 dry cacao beans. The decreasing order of free amino acids in PH-16 dry cacao beans is leucine, phenylalanine, glutamic acid, alanine, asparagine, tyrosine, gamma-aminobutyric acid, valine, isoleucine, glutamine, lysine, aspartic acid, serine, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…In the case of aspartic acid (Asp), a significant concentration could be detected from the second day in the SF, reaching a maximum of 2.12 mg/100 g (Tolopampa, Table 3 ). In contrast to this, this amino acid was not present in cacao from Guadalupe ( Table 2 ); on the other hand, the concentration of the amino acids in the SC varied among each place, highlighting that only in cacao from Guadalupe a concentration of 12.85 mg/100 g was found in the first days of fermentation, which disappeared on day 4, behavior similar to that reported by Brunetto et al (2020b) , who indicated that its degradation (or possible absence) favors the formation of hydrophobic amino acids ( John et al, 2019 ), in addition the low concentration reported is characteristic of a well-fermented bean ( de Araujo et al, 2021 ).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…In the case of aspartic acid (Asp), a significant concentration could be detected from the second day in the SF, reaching a maximum of 2.12 mg/100 g (Tolopampa, Table 3 ). In contrast to this, this amino acid was not present in cacao from Guadalupe ( Table 2 ); on the other hand, the concentration of the amino acids in the SC varied among each place, highlighting that only in cacao from Guadalupe a concentration of 12.85 mg/100 g was found in the first days of fermentation, which disappeared on day 4, behavior similar to that reported by Brunetto et al (2020b) , who indicated that its degradation (or possible absence) favors the formation of hydrophobic amino acids ( John et al, 2019 ), in addition the low concentration reported is characteristic of a well-fermented bean ( de Araujo et al, 2021 ).…”
Section: Resultssupporting
confidence: 66%
“…Moreover, a well-fermented cocoa bean presents a higher content of amino acids ( Tchouatcheu, Noah, Lieberei, & Niemenak, 2019 ); in addition, they are responsible for different physiological functions for humans ( Salaria, Boatwright, Thavarajah, Kumar, & Thavarajah, 2022 ), such as protein synthesis, repair tissues and nutrient absorption, among others ( Dala-Paula et al, 2021 ; Lopez & Mohiuddin, 2022 ). However, the concentration of amino acids varies by cacao origin, environmental conditions, and agricultural practices, among others ( de Araujo et al, 2021 ; Sari et al, 2023 ). Also, a standardized fermentation with a starter culture is a process that can regulate these variations ( Balcázar-Zumaeta, Pajuelo-Muñoz, et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The score of amino acid ratio coefficient SRC, SRC = 100 − CV × 100, where CV is the coefficient of variation of RC [45]. (3) Principal component analysis (PCA) was used to select several representative major components by a linear transformation of multiple variables [46][47][48]. Among 161 jujube cultivars, 8 amino acids were found to have high content.…”
Section: Methods For Evaluating Amino Acids Nutritionmentioning
confidence: 99%